2018
DOI: 10.5603/nmr.a2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

The use of 99mTc-phytate for assessment the protective effect of vitamin E against hepatotoxicity induced by methotrexat in rat

Abstract: Hepatotoxicity is one of the most common side effects of methotrexate (MTX) therapy in patients. The aim of this study was to evaluate the protective effect of vitamin E against MTX-induced hepatotoxicity using 99m Tc-phytate as a radiopharmaceutical agent in animals. Rats were divided into five groups as follows: control, solvent, Vit E (100 mg/kg), MTX (20 mg/kg) and Vit E + MTX. Animals were intraperitoneally injected with Vit E for 17 days before MTX injection and continued for 4 days. Tc-phytate was injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In rat model of MTX-induced liver injury therapeutic delivery of β-carotene, an important source of vitamin A in the human diet, with antioxidant properties, led to decreased hepatic MDA activity and increased hepatic SOD, CAT and GSH peroxidase activities under conditions of [ 153 ]. Amirfakhrian et al [ 177 ] showed the protective effect of vitamin E on liver architecture assessed by 99mTc-phytate functional imaging. Ismail et al [ 178 ] report that while thiamine pyrophosphate exhibited protective effects against MTX hepatotoxicity, thiamine alone was ineffective.…”
Section: Nutraceuticals Use To Counteract Mtx Toxicity In Experimenta...mentioning
confidence: 99%
“…In rat model of MTX-induced liver injury therapeutic delivery of β-carotene, an important source of vitamin A in the human diet, with antioxidant properties, led to decreased hepatic MDA activity and increased hepatic SOD, CAT and GSH peroxidase activities under conditions of [ 153 ]. Amirfakhrian et al [ 177 ] showed the protective effect of vitamin E on liver architecture assessed by 99mTc-phytate functional imaging. Ismail et al [ 178 ] report that while thiamine pyrophosphate exhibited protective effects against MTX hepatotoxicity, thiamine alone was ineffective.…”
Section: Nutraceuticals Use To Counteract Mtx Toxicity In Experimenta...mentioning
confidence: 99%
“…Despite of wide usage, Mtx has a range of side effects such as hepatotoxicity -nephrotoxicity (4,(6)(7)(8)(9). Therefore, it has been advised to prevent Mtx induced hepatotoxicity, it is using concomitant with antioxidants (10).…”
Section: Introductionmentioning
confidence: 99%